Optimization of hybrid photovoltaic-thermal systems integrated into buildings: Impact of bi-fluid exchangers and filling gases on the thermal and electrical performances of solar cells - Kokou Aménuvéla Toka; Yawovi Nougbléga; Komi Apélété Amou (AIMS Energy)
The low cooling efficiency of photovoltaic panels integrated into building façades restricts their electrical performance. The innovative approach of a dual-fluid photovoltaic-thermal system (BFPVT), incorporating bi-fluid cooling exchangers, appears to be a promising solution for jointly optimizing the electrical and thermal performance of PVT systems. However, despite the introduction of air heat shields to improve this performance, their limited efficiency makes them less competitive. We present a photovoltaic-thermal (PVT) system with a two-channel heat exchanger. The upper channel contains a stagnant fluid, which acts as a heat shield, while the lower, open channel ensures the continuous circulation or evacuation of heat transfer air. A copper metal plate separates the two channels. We examined the impact of various fluids employed as heat shields, including neon, argon, and xenon, in comparison to air, on the thermal and electrical performance of the collector. We employed numerical modeling of convective and conductive transfers to assess the average thermal efficiency of the BFPVT and the rise in PV temperature in the analyzed configuration. The equations were discretized using the implicit finite difference method and solved using the Thomas and Gauss-Seidel algorithms. The results demonstrated an 18% enhancement in thermal efficiency with the utilization of neon. In contrast, the employment of argon and xenon markedly reduced the mean temperature of photovoltaic cells by 4.82 ℃ and 4.87 ℃, respectively. This led to an increase in their electrical efficiency by 0.33% in comparison to air. Thus, argon is regarded as the optimal choice for optimizing electrical efficiency, taking into account both economic and environmental considerations.